Comparison of genomic and antigenic properties of Newcastle Disease virus genotypes II, XXI and VII from Egypt do not point to antigenic drift as selection marker. Issue 2 (25th June 2021) - Naguib, Mahmoud M.; Höper, Dirk; Elkady, Magdy F.; Afifi, Manal A.; Erfan, Ahmed; Abozeid, Hassanein H.; Hasan, Wafaa M.; Arafa, Abdel‐Satar; Shahein, Momtaz; Beer, Martin; Harder, Timm C.; Grund, Christian
Abstract: Newcastle disease (ND), caused by avian orthoavulavirus type‐1 (NDV), is endemic in poultry in many regions of the world and causes continuing outbreaks in poultry populations. In the Middle East, genotype XXI, used to be present in poultry in Egypt but has been replaced by genotype VII. We investigated whether virus evolution contributed to superseding and focussed on the antigenic sites within the hemagglutinin‐neuraminidase (HN) spike protein. Full‐length sequences of an NDV genotype VII isolate currently circulating in Egypt was compared to a genotype XXI isolate that was present as co‐infection with vaccine‐type viruses (II) in a historical virus isolated in 2011. Amino acid differences in the HN glycoprotein for both XXI and VII viruses amounted to 11.7% and 11.9%, respectively, compared to the La Sota vaccine type. However, mutations within the globular head (aa 126–570), bearing relevant antigenic sites, were underrepresented (a divergence of 8.8% and 8.1% compared to 22.4% and 25.6% within the protein domains encompassing cytoplasmic tail, transmembrane part and stalk regions (aa 1–125) for genotypes XXI and VII, respectively). Nevertheless, reaction patterns of HN‐specific monoclonal antibodies inhibiting receptor binding revealed differences between vaccine‐type viruses and genotype XXI and VII viruses for epitopes located in the head domain. Accordingly, compared to Egyptian vaccine‐type isolates and the La Sota vaccine reference strain, single aa substitutions in 6 of 10 described neutralizing epitopes of HN were found. However, the same alterations in neutralization sensitive epitopes were present in old genotype XXI as well as in newly emerged genotype VII isolates. In addition, isolates were indistinguishable by polyclonal chicken sera raised against different genotypes including vaccine viruses. These findings suggest that factors other than antigenic differences within the HN protein account for facilitating the spread of genotype VII versus genotype XXI viruses in Egypt.